PENYELESAIAN SENGKETA JUAL BELI TANAH WARISAN TANPA PERSETUJUAN AHLI WARIS YANG LAIN (STUDI KASUS PUTUSAN NOMOR : 1300/Pdt.G/2023/PA.Pt) : PENYELESAIAN SENGKETA JUAL BELI TANAH WARISAN TANPA PERSETUJUAN AHLI WARIS YANG LAIN (STUDI KASUS PUTUSAN NOMOR : 1300/Pdt.G/2023/PA.Pt) - Salsabila Biuti Oktamiarsa Ni'mah (CV Rewang Rencang, 2024)
This study was conducted using normative juridical and library methods. This study shows that disputes over inherited land can be resolved by a civil lawsuit in a religious court without the consent of other heirs. According to this study, each heir must agree with the sale and purchase transaction of inherited land so that there are no problems in the future. Buyers of undivided inherited land can obtain legal protection by cancelling the sale and returning the property they bought. In addition, they found that buyers should be careful when buying undivided inherited land as it may stop the sale and purchase. Keywords: Inheritance, Islamic Law, Buyer Legal Protection